Distribution of Serum Creatinine Levels in Pregnant Women with Pregnancy Induced Hypertension - Balayasothini, V.; Madhurahini, R.; Jeneni, J.; Arasaratnam, V.; Muhunthan, K.; Aranraj, T. (University of Ruhuna, Sri Lanka, 2024)
Background: In Sri Lanka, pregnancy-related hypertension, notably preeclampsia, is a prominent health concern, posing substantial risks to maternal and fetal well-being. Objective: To determine the distribution patterns of serum creatinine in normal pregnant women and women diagnosed with pregnancy-induced hypertension Methods: This is a population based, analytical, cross-sectional study. In this study, 34 normal pregnant women (group 1) and 34 pregnant women with pregnancy-induced hypertension (group- 2; 140/90 mmHg on two or more occasion and without proteinuria) were enlisted. Serum creatinine levels were estimated using colorimetric Jaffe alkaline picric acid kinetic method. Pre- pregnancy weight and height measurements were taken from the clinical records and the pre- pregnancy BMI values of the women were calculated. Mean serum creatinine levels were compared between group 1 and group 2 by independent sample t-test. Results: The serum creatinine level ranged from 0.38-1.14 mg/dL among the total of 68 women. Mean serum creatinine levels of group 1 and group 2 women were 0.53±0.06 and 0.76±0.17 mg/dL, respectively. A statistically significant difference (p<0.001) in the mean serum creatinine levels was observed between the two groups of the pregnant women. The selected women were classified into underweight (<18.5 kg/m2 ), normal (18.5-24.9 kg/m2 ), overweight (25.0-29.9 kg/m2 ), obese (30.0-39.9 kg/m2 ) and extremely obese (>40.0 kg/m2 ). Majority of the women in group 1, exhibited normal BMI mean±SD (21.95±2.10 kg/m2 ) while those in group 2 were overweight (26.881.05 kg/m2 ) and the differences in mean serum creatinine levels within these BMI groups were not differ significantly (p>0.05). Conclusions: Our study highlights a significant elevation in serum creatinine level among individuals with pregnancy induced hypertension than the normotensive group suggesting its potential utility as a marker for early detection of pre-eclampsia-like pregnancy-induced hypertensive diseases.
Keywords: Body mass index; Pre-eclampsia; Pregnancy induced hypertension; Pregnant women; Serum creatinine